Automatic messaging system by detecting the road accidents for vehicle applications. (2023) - Karthik, M.; Sreevidya, L.; Vinodha, K.; Thangaraj, M.; Hemalatha, G.; Sena, T. Viswak
Abstract: The emerging advancements in innovation has changed our lives drastically making it ease. Yet in this forefront world the rate of automobile accidents is still increasing resulting in increased fatality rate majorly due to untimely attention of emergency services. Our project will provide the best possible answer to this problem. When an automobile collides with another vehicle, the MEMS sensor senses this and sends the data, which is then processed by Arduino, according to this project. The Arduino sends an alarm message to a police control room or a rescue squad via the GSM Module, which includes the position. As a result, as soon as the police receive the information, they can use the GPS Module to track down the location. Then, once the location has been confirmed, the necessary steps will be taken. The project alerts the emergency services and the family members for immediate help by sending the location when an accident occurs.